Effect of temperature on tribological performance of polyetheretherketone-polybenzimidazole blend. (January 2019) - Jean-Fulcrand, Annelise; Masen, Marc A.; Bremner, Tim; Wong, Janet S.S.
Abstract: Polyetheretherketone (PEEK) is one of the most commonly used High Performance Polymers (HPP) although its high temperature performance is poor. In this study, polybenzimidazole (PBI), a HPP with one of the highest glass transition temperatures currently available, is blended to PEEK to form a 50:50 blend (TU60). Tribological performance of the blend (TU60) was investigated by rubbing it against steel at temperatures up to 280 °C. Results obtained are compared to those from neat PEEK and neat PBI. All three polymers were thermally stable during the duration of tests. However chemical analyses on polymeric transfer layers on steel surfaces and polymer debris suggest polymer degradation. The degradation observed is shear-assisted, possibly promoted by shear heating. Indeed the estimated interfacial temperature based on Jaeger model was above the melting point of PEEK in some cases. TU60 outperforms PEEK in all test conditions and PBI at 280 °C. TU60 formed transfer layers on steel similar to that of PEEK. When contact temperature is closed to the melting point of PEEK, PEEK in the TU60 creates a low strength transfer layer which acts as an interfacial lubricant. This reduces friction which in turn reduces PBI degradation in TU60 at high temperature. This work provides a strategy for creating interfacial layers to improve polymer tribological performance while maintaining the integrity of the polymer. Highlights: Tribology of a PEEK-PBI blend rubbed against steel at temperatures up to 280 °C were investigated. PEEK, PBI and the blend are thermal stable. Chemical analysis shows they degrade under shear. The blend outperforms neat PBI at 280 °C due to the formation of PEEK transfer layer on steel. PBI degradation, and wear of both steel and the blend are reduced due to PEEK transfer layer. A low Tm polymer blends with high Tg polymer gives good high temperature tribological performance.